Peculiar Role of the Metallic States on the Nano‐MoS2 Ceramic Particle Surface in Antimicrobial and Antifungal Activity. Issue 4 (7th August 2014) - Karwowska, Ewa; Kostecki, Marek; Sokołowska, Aleksandra; Chodun, Rafał; Zdunek, Krzysztof
<x xml:space="preserve">Abstract</x> This study concerns the interactions of two chemically different materials hBN (covalent‐ionic bonds) and MoS2 (covalent‐ionic and dispersive bonds) with bacteria and fungi. The materials used in the study were in the form of micro‐ and nanocrystals. Countable inactivation of microorganisms (Staphylococcus aureus, Sarcina lutea, Aspergillus niger, Escherichia coli) took place only in the case of MoS2 nanosheets. The authors of the study suppose that the bioactivity of nano‐MoS2 can be associated with the presence of "metallic states, " which are present only on their surface.